EFEKTIVITAS FERRI KLORIDA (FeCl3)DALAM MENURUNKAN KADAR CHEMICAL OXYGEN DEMAND (COD) PADA LIMBAH CAIR LAUNDRY - Ayu Larasati; Yusniar Hanani Darundiati; Hanan Lanang Dangiran (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2017)
Laundry liquid waste contained high level of COD which can effect on water contamination. Based on the preliminary studies, COD level of liquid waste in Laundry Zone was 1.494 mg/l and 992 mg/l. This level exceeds standart quality of COD in Laundry liquid waste is 100 mg/l. Therefore, it was necessary to wastewater treatment, one of them with coagulation-flocculation system using ferric chloride coagulant. The purpose of this study was to determined the effectiveness of ferric chloride to reduced COD level in laundry liquid waste. The type of research was true experimental research with pretest-postest with control group design. The sample in this research was part of wastewater from Laundry Zone that taken directly through the washing machine outlet pipe. Total sample for 6 treatment (0,5 gr; 0,7 gr; 0,9 gr; 1,1 gr; 1,3 gr; dan 1,5 gr) with 4 replication was 32 samples. Data analysis used Kruskal Wallis test showed that there was difference average in decreasing COD level of laundry liquid waste with various dose of ferric chloride (p-value = 0,005). The result of Man Whitney test, showed that groups between dose variation that have significant difference in decreasing COD level of laundry liquid waste (p≤0,05) was control group and 0.5 gr treatment group with each other the treatment groups. The average COD after treatment has decreased gradually as more doses of ferric chloride. The largest efficiency was in the dose 1,5 gr with a decrease percentage was 73.79% or decreased COD to 249.75 mg/l.